Daring to care : American nursing and second-wave feminism - Malka, Susan Gelfand (University of Illinois Press, 2007)
Arguing that feminism helped to end nursing's subordination to medicine and provided nurses with greater autonomy and professional status, the author examines the impact of second-wave feminism on the nursing field since the 1960s.
Keywords: Nursing -- United States -- History.; Feminism -- United States -- History.; Nurses -- United States -- Social conditions.; History of Nursing; Education, Nursing -- history; Feminism -- history; History, 20th Century; Women's Rights -- history; United States; Féminisme -- États-Unis -- Histoire.; Infirmières -- États-Unis -- Conditions sociales.; Médecine -- Histoire -- 20e siècle.; SOCIAL SCIENCE / General; Feminism; Nurses -- Social conditions; Nursing; Berufsausbildung; Krankenpflege; Frauenbewegung; Feminismus; USA; History